Święcenia duchowne Łukasza Watzenrode (1447-1512). Przyczynek do biografii biskupa warmińskiego - Kaczmarek, Krzysztof (Archiwa, Biblioteki i Muzea Kościelne, 2017)
Historians have been interested in the Bishop of Warmia Łukasz Watzenrode for many years, mainly because of his close affinity with Nicolas Copernicus and the complicated history of the Diocese of Warmia during this bishop’s reign. The part of Łukasz’s life which preceded his bishop’s election has not aroused such interest. And therefore this article is about this less known fragment of his biography. It deals with the issues related to Watzenrode taking lesser vows and being ordained a priest. The information about bishop Watzenrode having all ordines, including the priesthood, at the end of the 1470s was questioned. The research showed that it was not until the spring of 1487 that he received all higher ordinations. This fact should be connected with the plans of appointing him to the Episcopal capital of Lidzbark Warmiński as a successor of Mikołaj Tungen.